Studying the temporal bias of the steady-state approximation of 234Th-derived carbon export during phytoplankton blooms - Guo, Mingxian; Xiu, Peng; Zhou, Kuanbo (Frontiers in Marine Science, 2025)
The 234Th–238U pair technique is widely used in estimating particulate organic carbon (POC) flux, typically with a steady-state (SS) assumption. There is often a temporal bias between the SS-derived and actual POC fluxes caused by neglecting the temporal change in 234Th. However, this temporal bias has not been fully investigated due to the lack of continuous sampling of 234Th profiles and sediment traps. Here, we develop a radioactive trace model of 234Th built on a physical–biogeochemical model to simulate the scavenging of 234Th in the water column by POC sinking processes at the South East Asia time series (SEATS) site. The seasonal patterns of the 234Th profiles simulated by the model generally compared well with in situ observations. Analysis based on the model simulation suggests that the temporal bias can be depicted and reproduced in a simplified 234Th continuity equation. By obtaining an analytical solution for the SS-derived POC flux from the simplified 234Th equation, we found that the temporal bias results from the phase difference in time between the SS-derived and direct sinking POC fluxes. To provide a method that does not need repeated samplings to reduce this temporal bias for in situ observations, a modification term was constructed for the SS-derived POC flux from the analytical solution. Applying this term to the data obtained at the Bermuda Atlantic time series and SEATS reduced the bias by up to 67% and 34%, respectively. This study provides a feasible way to improve 234Th-derived POC flux under the SS assumption.